2013
DOI: 10.1016/j.forsciint.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Lumicyano™: A new fluorescent cyanoacrylate for a one-step luminescent latent fingermark development

Abstract: Latent fingermarks developed by cyanoacrylate fuming often lack contrast; therefore further enhancement is required, such as dye staining. This second step is part of the conventional detection sequences performed by forensics practitioners. Dye-staining or powder dusting aims at improving contrast and at increasing the legibility of details, yet their use may at times be limited. Indeed powder dusting may not be effective due to unexpected adherence to the background, and poor affinity to the cyanoacrylate. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…The additional number of marks by the second treatment in process A (Lumicyano 4% atmospheric) was unexpected; however, the increased detection by the third treatment (BY40) was expected as observed in other trials [15,16]. The increased detection rate by the second treatment did not result in over-fumed marks and may be explained by the fact that the cyanoacrylate polymer in Lumicyano grows in the z- direction above the ridges, rather than in the x-y plane [12,37]. After the first treatment in process A, some marks may have been weakly developed that are not readily observed by visual and/or fluorescence examination.…”
Section: Preliminary Work Into Vacuum Conditions From Deposited Marksmentioning
confidence: 55%
See 1 more Smart Citation
“…The additional number of marks by the second treatment in process A (Lumicyano 4% atmospheric) was unexpected; however, the increased detection by the third treatment (BY40) was expected as observed in other trials [15,16]. The increased detection rate by the second treatment did not result in over-fumed marks and may be explained by the fact that the cyanoacrylate polymer in Lumicyano grows in the z- direction above the ridges, rather than in the x-y plane [12,37]. After the first treatment in process A, some marks may have been weakly developed that are not readily observed by visual and/or fluorescence examination.…”
Section: Preliminary Work Into Vacuum Conditions From Deposited Marksmentioning
confidence: 55%
“…In the early 1990s, Weaver and Clary [10] reported a one-step fluorescent process using a solid cyanoacrylate polymer and 3 M styryl dyes. More recently, research has investigated other one-step processes available such as Polycyano (Cyano UV, Foster and Freeman, U.K.) [11,12], fuming orange and CN yellow (Aneval, Inc., Illinois, US) [13] and Lumicyano (Crime Scene Technology, France) [14]. Most of these products require heating temperatures of !230 8C with the exception of Lumicyano where a traditional hot plate temperature of 120 8C is required.…”
Section: One-step Processmentioning
confidence: 99%
“…One species was marked using Lumicyano TM (Crime Scene Technology q ), a cyanoacrylate fluorescent glue that reacts to ultraviolet light (electronic supplementary material, S2) [33]. The marking consisted of a small spot (1 mm Marking was alternated between the two species between trials.…”
Section: (E) Heterospecific Conditionmentioning
confidence: 99%
“…Midkiff and Codell (1995) observed that thickness, type and consistency of adhesive affect the quality of cyanoacrylate-fumed developed fingermarks. A novel luminescent cyanoacrylate such as lumicyano was used to develop latent fingerprints on glass and a number of semiporous and nonporous surfaces in a single processing step without any further treatment (Prete et al 2013). One-step fluorescent cyanoacrylate fuming method was used to develop high-quality fluorescent prints on a wide range of nonporous surfaces including trash bags, sandwich bags, sheet protectors, bubble wrap and textured plastic.…”
Section: Evaluation Of Cyanoacrylate Fuming Methodsmentioning
confidence: 99%